2022
DOI: 10.3390/bs12080297
|View full text |Cite
|
Sign up to set email alerts
|

Empirical Investigation of Work-Related Social Media Usage and Social-Related Social Media Usage on Employees’ Work Performance

Abstract: The trend of using social media in the workplace is now becoming ubiquitous. Along witbenefits, social media also has negative consequences. Employees use social media for both work and social purposes. Therefore, using a quantitative approach, this study explores the impact of work-related social media usage and social-related social media usage on employees’ work performance. This study also investigates the mediating effect of extra-role behaviors on social media usage (professional and personal purpose) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 73 publications
0
12
0
Order By: Relevance
“…Later, some other scholars researched to discover the influence of perceived usefulness on insolence to the online acquisition and concluded that PU influences attitudes toward an online purchase in a lively manner. Similarly, internet shopping gives shoppers more excellent product choices than physical stores, allowing them to compare different available brands and choose the best fit for them just with a few clicks of fingers [49,50].…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…Later, some other scholars researched to discover the influence of perceived usefulness on insolence to the online acquisition and concluded that PU influences attitudes toward an online purchase in a lively manner. Similarly, internet shopping gives shoppers more excellent product choices than physical stores, allowing them to compare different available brands and choose the best fit for them just with a few clicks of fingers [49,50].…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…External networking through Facebook, LinkedIn, and Twitter exposes employees to diverse ideas and perspectives, stimulating creativity and innovation. Furthermore, social media use in the workplace can enhance employees' thriving, defined as a state of vitality and learning (Dantas et al, 2022). Thriving employees are more likely to be engaged, creative, and satisfied with their work and life.…”
Section: Performance and Satisfactionmentioning
confidence: 99%
“…Previous related literature were reviewed on performance management of employees, its variables, social media and its influences on employee's performance. A) Dantas, R., et al (2022). The study explored the mediating effect of extra-role behaviours on work-related social media usage and social-related social media usage work performance relationship.…”
Section: Literature Reviewmentioning
confidence: 99%